Genomewide association study of HLA alloimmunization in previously pregnant blood donors. Issue 2 (22nd November 2017) - Seielstad, Mark; Page, Grier P.; Gaddis, Nathan; Lanteri, Marion; Lee, Tzong‐Hae; Kakaiya, Ram; Barcellos, Lisa F.; Criswell, Lindsey A.; Triulzi, Darrell; Norris, Philip J.; Busch, Michael P.; ,
Abstract : BACKGROUND: Alloimmunization through blood transfusion, transplantation, or circulating fetal cells during pregnancy is a significant concern. Some exposed individuals make alloantibodies while others do not, implying variation in genetic risk factors. STUDY DESIGN AND METHODS: We conducted a genomewide association study (GWAS) of 9, 427, 497 single‐nucleotide polymorphisms (SNPs) to identify genetic variants for HLA alloimmunization in previously pregnant blood donors with (n = 752) and without (n = 753) HLA Class I or II alloantibodies. RESULTS: A SNP in the neurexophilin 2 (NXPH2) gene surpassed genome‐wide significance (p = 2.06 × 10 −8 ), with multiple adjacent markers p < 10 −6, for women with anti‐Class I alloantibodies only. Little is currently known about the function of NXPH2, although gene family members have been shown to impact immunity. SNPs in the E2F7 gene, a transcription factor related to cell cycle control and cellular proliferation, also approached genomewide significance (p = 2.5 × 10 −7 ). CONCLUSION: Further work to extend the GWAS approach and to characterize variants in NXPH2 and E2F7 in the context of alloantibody formation is warranted.